Análise dos procedimentos de estimativa da idade cronológica do indivíduo pela avaliação dentária no Instituto Médico Legal de Fortaleza - Solon, Silvana Maria Neves (2008)
The estimation of chronological age can be defined as the process that evaluates the stage of evolution or involution of a body. The age determination by a dental evaluation is a technical inspection that can be performed by a Surgeon-Dentist, in accordance with the law of dentistry practice. This examination is carried through in legal medicine institutes with high frequency. In the Institute of Legal Medicine (IML) of Fortaleza - Ceará, this percentage is 32.4% of all examinations. This study aimed to analyze the procedures for estimation of chronological age by dental evaluation conducted in IML of Fortaleza, based on procedures and methods for estimating the chronological age as described in literature. A literature review was performed and it has demonstrated that the estimation of chronological age has different nuances, it has been studied for a long time, and there are methods with accurate results that are required in many policy and judicial court processes. The most important information for age determination by examination of permanent teeth is distributed in their evolution stages: mineralization, dental eruption and dental late alterations. The technical term DENTITION has a dynamic sense, since it defines several stages from the thickening of the epithelium of the basal layer to the dental loss. DENTURE is static, as it defines only a phase of life of the individual: it is all the teeth at that time. The development of dental radiology has introduced new methods for estimating age, which increased the age determination accuracy. The oral examination is the only method currently used to age determination in the IML - Fortaleza. This study concluded that the oral examination procedures need to be complemented by radiological examinations that show reliable results and accurate age determination.